Smart DevOps: AI-Powered Orchestration for Optimized Cloud Environments - Patel, Ismail (MZ Journal of Artificial Intelligence, 2024)
In the realm of cloud computing, the integration of Artificial Intelligence (AI) with DevOps practices is reshaping operational paradigms, driving towards greater efficiency and optimization. This paper explores the concept of Smart DevOps, where AI-powered orchestration transforms traditional DevOps workflows into dynamic and proactive systems. AI technologies such as machine learning and predictive analytics enable automated decision-making, real-time insights, and optimized resource management in cloud environments. By leveraging AI-driven orchestration, organizations can streamline software deployment, enhance scalability, and preemptively resolve operational issues. This abstract delves into the significant benefits of Smart DevOps, highlighting its role in fostering agility, resilience, and cost-effectiveness while paving the way for innovation and competitive advantage in the digital age.